(untitled) (Journal of the College of Basic Education, 2024)
The research aimed to identify “the effect of the Cosgrove model on the acquisition of chemical concepts among first-year middle school female students and their inductive thinking.” To achieve the research goal, the two null hypotheses mentioned later were formulated. The research sample consisted of (52) students, after statistically excluding the failed students. The female students of Division (B) were randomly assigned as an experimental group, their number was (26), and the female students of Division (C), which were (26), as a control group. The two groups were rewarded in the variables (intelligence, Previous achievement, previous concepts, inductive thinking). The researcher prepared two research tools, the first of which is a test for the acquisition of chemical concepts according to the content analysis of the chemistry textbook for the first intermediate grade, consisting of (60) objective items of the multiple-choice type with four alternatives, and the second is an inductive thinking test consisting of (30) items of the multiple-choice type. The validity and stability of the two tools were confirmed before application, and they were applied to the research sample after completing the experiment to obtain results. The results of the research resulted in the superiority of the female students of the experimental group who studied according to the Cosgrove model over the female students of the control group who studied according to the usual method in testing the acquisition of concepts. Chemistry for the first intermediate grade, and they also excelled in the inductive reasoning test. Based on the above, the researcher presented a set of recommendations and proposals.